Use of virtual academic media, adaptability to university life, and addiction to social media as predictors of academic procrastination in Peruvian university students - Turpo Chaparro, Josué Edison (My University, 2025)
This study examines how the use of virtual academic media, adaptability to university life, and social media addiction predict academic procrastination among Peruvian university students. Using a quantitative, correlational design, the research analyzes the relationships between these variables and identifies the most significant predictors of procrastination in the academic context. The findings contribute to understanding the behavioral and technological factors influencing students’ academic performance in higher education
Keywords: Procrastination; Adaptability; Psychology; Addiction; Social media; Social psychology; Applied psychology; Addictive behavior; Higher education; Medical education; Developmental psychology; The Internet; Computer-mediated communication; Academic achievement; Public university; Graduate students; Social influence; Media use; Procrastination; Adaptability; Addiction; Social media; Addictive behavior; Higher education; The Internet; Social Sciences Psychology Clinical Psychology Perfectionism, Procrastination, Anxiety Studies; Social Sciences Social Sciences Sociology and Political Science Impact of Technology on Adolescents; Social Sciences Psychology Social Psychology Technostress in Professional Settings